PENINGKATAN KETERAMPILAN MENULIS PUISI MELALUI STRATEGI PIKIRAN PLUS DENGAN MENGGUNAKAN MEDIA GAMBAR PERISTIWA - Akbar, Syafaat Yusufa; Herdiana, Nia; Yunus, Syarifudin (Cahaya Ilmu Bangsa Institute, 2025)
Based on the results of the study, the application of the Mind Plus strategy using event picture media proved effective in improving students' poetry writing skills. Through the processes of observing pictures, asking questions, developing ideas, and composing poems, students became more creative, systematic, and directed in expressing their feelings and thoughts into literary works. The use of visual media as a stimulus helped students more easily find main ideas and enriched their imagination in choosing diction, building atmosphere, and forming aesthetic poem structures. The implication of these results indicates that the Mind Plus strategy assisted by visual media is feasible to be implemented in poetry writing instruction at school. This strategy can create a more active, enjoyable, and motivating learning atmosphere, encouraging students to be more confident in producing creative works. Teachers are expected to adopt this method to optimally develop students' literacy skills, thereby making poetry writing learning more contextual, inspiring, and relevant to the development of students' creativity.